A four-port wideband filtering monopole MIMO array for sub-6 GHz 5G communications - Ayyappan, Jasmine Vijithra; Mohammed, Gulam Nabi Alsath; Subbaraj, Sangeetha (International journal of microwave and wireless technologies, 2023)
This communication presents the significance of a four-port 2×2 multiple input multiple output antenna operating in mid-band frequency for 5G handheld device application. A microstrip-fed reference truncated decagonal monopole antenna operating at 3.9 GHz and a modified split-ring resonator (SRR)-based low-pass filter that excites at a cut-off frequency of 6.5 GHz are designed. On introducing a stub line in the SRR structure, the proposed filter shows a good out-of-band rejection beyond 6.5 GHz. By integrating the filter into the reference monopole, a wideband filtering monopole with improved stopband performance is obtained. A four-port MIMO array is constructed by orthogonally positioning the antenna with a center-to-center separation of 0.25λ0. To improve isolation, a pair of inverted L-stubs of varying lengths is introduced. The closed loop formed by the interconnection of stubs enhances isolation within the frequency range of 3–3.5 GHz. The fabricated prototype fosters an impedance bandwidth of 66.67%, isolation >18.5 dB, an average suppression of 15 dB, an average peak gain >3.7 dB, envelope correlation coefficient < 0.015, Actual Diversity Gain (ADG) > 9.9 dB, Effective Diversity Gain (EDG) > 8.8 dB, and efficiency >88%. The proposed design is suitable for 5G sub-6 GHz applications such as n48, n77, n78, n79 bands, WiMAX, and LTE bands 42, 43, 46, 47, 48.